Peroxisomes contribute to biosynthesis of extracellular glycolipids in fungi. Issue 1 (3rd June 2014) - Freitag, Johannes; Ast, Julia; Linne, Uwe; Stehlik, Thorsten; Martorana, Domenica; Bölker, Michael; Sandrock, Björn
Summary Many microorganisms secrete surface‐active glycolipids. The basidiomycetous fungus Ustilago maydis produces two different classes of glycolipids, mannosylerythritol lipids (MEL) and ustilagic acids (UAs). Here we report that biosynthesis of MELs is partially localized in peroxisomes and coupled to peroxisomal fatty acid degradation. The acyltransferases, Mac1 and Mac2, which acylate mannosylerythritol with fatty acids of different length, contain a type 1 peroxisomal targeting signal (PTS1). We demonstrate that Mac1 and Mac2 are targeted to peroxisomes, while other enzymes involved in MEL production reside in different compartments. Mis‐targeting of Mac1 and Mac2 to the cytosol did not block MEL synthesis but promoted production of MEL species with altered acylation pattern. This is in contrast to peroxisome deficient mutants that produced MELs similar to the wild type. We could show that cytosolic targeting of Mac1 and Mac2 reduces the amount of UA presumably due to competition for overlapping substrates. Interestingly, hydroxylated fatty acids characteristic for UAs appear in MELs corroborating cross‐talk between both biosynthesis pathways. Therefore, peroxisomal localization of MEL biosynthesis is not only prerequisite for generation of the natural spectrum of MELs, but also facilitates simultaneous assembly of different glycolipids in a single cell.